Professionalism of Islamic education teachers in teaching to special needs students - Dzulkifli, Izuli; Mohd Fakhruddin, Fathiyah (Human Resource Management Academic Research Society, 2024)
Teacher professionalism in special education plays a crucial role in ensuring the effectiveness of instruction for special needs students. In the context of Islamic education, the challenge of meeting the learning needs of special needs students requires teachers who are not only knowledgeable in academic matters but also possess pedagogical skills based on various disabilities. This paper aims to discuss the professionalism of Islamic education teachers within the context of special education and their roles in ensuring to deliver effective teaching for students. Using a literature review and case study analysis, this paper identifies the competencies that teachers must master, including communication skills, creativity in teaching, and a deep understanding of the psychological and emotional needs of special education students. Islamic education teachers need to master appropriate teaching techniques, such as the use of interactive teaching aids and methods of delivery that are easily understood by students with diverse abilities. The role of teachers extends beyond the delivery of knowledge; but they also serve as guides who foster the spiritual and moral development of special needs students. The implications of this paper highlight that enhancing the professionalism of Islamic education teachers is essential for strengthening special education in Malaysia. In conclusion, continuous professional development in pedagogical skills is necessary for teachers to play a more significant role in promoting inclusive and effective education.